Effects of Isothermic Irrigation on Core Body Temperature During Endoscopic Urethral Stone Treatment Surgery Under Spinal Anesthesia: A Randomized Controlled Trial - canturk, Mehmet; hakki, Meltem; kocaoglu, Nazan (Urology Journal, 2020)
Purpose? Isothermic irrigation decreases the reduction in core temperature and shivering in patients undergoing transurethral resection of prostate gland but this effect has not been studied in patients undergoing endoscopic urethral stone treatment surgery. The current study is designed to study the effect of isothermic hydration on core temperature in patients scheduled for endoscopic urethral stone treatment surgery under spinal anesthesia. Materials and Methods? Sixty patients allocated randomly into two groups. In GroupW (n = 30) irrigation fluid at 37°C was used whereas at room temperature in GroupRT (n = 30). Spinal anesthesia was performed at L3-L4 interspace with 15mg of hyperbaric bupivacaine. Core temperature, shivering, and hemodynamic parameters were measured every minute until 10th minute and five minute intervals until the end of operation. Shivering and surgeon comfort was also recorded. The primary outcome was the core temperature at the end of surgery. Frequencies, means, standard deviations, percentages, chi-square tests, independent samples t-test, and Mann Whitney U tests were used where eligible for the statistical analysis. Results? Baseline core temperature was 36.6 ± 0.4°C in GroupW and 36.6 ± 0.5°C in GroupRT (P = .097) which decreased to 36.0 ± 0.5°C and 35.2 ± 0.7°C respectively (P = .018) at the end of operation. Shivering was observed in 36.7% (n = 11) in GroupRT and 6.7% (n = 2) in GroupW (P = .012). Hemodynamic parameter changes and demographic data were not significant between groups. Conclusion? Isothermic irrigation decreases both the reduction in core temperature and the incidence of shivering while increasing the surgeon comfort.